PENINGKATAN KEMAMPUAN GURU DALAM MEMBUAT RENCANA PELAKSANAAN PEMBELAJARAN (RPP) TEMATIK 1 HALAMAN MELALUI WORKSHOP DARING DENGAN VARIASI MODEL JIGSAW DI UNIT PELAKSANA TEKNIS DAERAH (UPTD) SEKOLAH DASAR (SD) NEGERI GENTENG 2 BANGKALAN - Arifin , Zainal (re-JIEM (Research Journal of Islamic Education Management), 2020)
This research is a school action research with the main instrument being the task of making 1-page thematic lesson plans. There are 2 coaching cycles and the results of the study show that the teacher’s ability to make 1-page thematic lesson plans can be improved through online workshops with variations of the jigsaw model. This is evidenced in the implementation of school action research which consists of 2 cycles showing an increase from cycle I to cycle II based on the results of assignments carried out in making thematic lesson plans, namely from 7 teachers there are 3 teachers or 42.86% in the low category, every 2 teachers or 28.57% in the medium and high categories. After the second cycle was carried out, the data obtained from the teacher’s ability to make 1-page thematic lesson plans as follows that there were no teachers in the low category, 1 teacher or 14.28% in the medium category, and 6 teachers or 85.71% in the high category, therefore the cycle was stopped, because it has reached the expected success indicator, which is more than 75% in the high category. Teachers should continue to improve their competence in making 1-page Thematic lesson plan.